Situation of Food Provision in Child Care Centers in Thailand - Kunpeuk, Watinee; Cetthakrikul, Nisachol; Phulkerd, Sirinya; Pongcharoen, Tippawan; Udomkarnjananan, Sarawadee; Ponguttha, Suladda; Thamarangsi, Thaksaphon (Journal of Health Science of Thailand, 2017)
At present, the government sector has developed standards for food provision in child care centers (CCCs) to ensure that food provided to children meets the nutritional standards. However, existing evidence illustrates that certain CCCs offer diets high in added sugar, fat or salt which are one of major factors contributing to overweight and obesity among children. The purpose of this study was to assess the situation of food provision in the CCCs in Thailand. A cross-sectional, self-reported survey was conducted to gather demographic characteristics and food management information from 410 CCCs across six regions of Thailand. Descriptive statistics and correlation were used for data analysis. The findings demonstrated the large- and middle-size CCCs located in urban areas offered meats, vegetables and fruits more often than the small-size CCCs in the rural areas. The highest percentage of the provision of Thai desserts, sweetened yoghurts, sweetened milks and soda drinks was found in urban CCCs (67.0%, 12.7%, 10.2% and 1.7%, respectively) and large-size CCCs (75.8%, 3.0%, 18.1% and 12.1%, respectively). The largest proportion of sweetened beverages, snacks and desserts was reported in the rural CCCs (14.4%, 12.7% and 9.9%, respectively) and the small-size centers (17.5%, 13.4% and 10.1%, respectively). Caregivers who were working in the large-size and urban CCCs received more nutrition training opportunities than those who were in the small-size and rural centers. Several types of energy-dense foods were still served by staff with training experience in nutrition. Therefore, there is a need to develop a monitoring and evaluation system for food management standards in the CCCs. Local nutritionists or dietitians are encouraged to get involved in the management of feeding practices in these child care settings. Opportunities for nutrition training and refresher courses should be provided for both staff in the CCCs and officers from the local administration. Quality of nutrition training is also required and the training should be provided to relevant staff from all types and levels of CCCs.